Glossolalalararium Pandemiconium: A Meaningfully Irreverent, Queerelously Autoethnographic Essamblage for Trying Times. (September 2021) - Murray, Peta
If there is any throughline to COVID-19, it lies within a narrative of capriciousness. To explore the paradox of the pandemic as proliferation meets obliteration, I alternate randomization with redaction within a riotous essamblage combining essayistic principles of "prepositional thinking" with bricolage. Neologisms meet textracts of responses to the 21 prompts of the Massive and Micro experiment. Glossolalalararium Pandemiconium comes with a helping of "lala" in a froth of babble, doubt, rage, and whimsy. It is a textual grappling with the shock and awe of the everyday, girded by a notion of "meaningful irreverence" that underpins my current research.